Prevention of suppurative complications in hip joint arthroplasty - Azizov, Mirkhakim; Makhsudov, Shuhratbek (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2010)
Within 2008–2009, 420 operations of hip joint arthroplasty in different pathologies were made at the Department of Adult Orthopaedics of the Institute. In order to prevent possible complications, the authors developed a complex of prophylactic measures. Administration of antibiotics in compliance with the elaborated scheme in 50 patients was followed by their blood sampling to determine the antibiotic concentration in tissues. Initial concentration was achieved 40 minutes after the administration, it being the most favourable moment for beginning the operation. The authors’ method of antibiotic prophylaxis ensures an effective concentration in the surgical intervention area at the period of potential contamination. The use of controlled hypotonia in spinal anaesthesia and «delayed» infusion therapy reduce blood loss during the operation.